2018
DOI: 10.1016/j.corsci.2018.03.025
|View full text |Cite
|
Sign up to set email alerts
|

The galvanic corrosion of welded ultra-high strength steels used for automotive applications

Abstract: In situ Scanning Vibrating Electrode Technique and time lapse photography were used to study the galvanic corrosion of high strength low alloy (HSLA) steel, laser welded to hot stamped ultra high strength steel (UHSS) in 0.017 M NaCl. Samples of HSLA welded to UHSS exhibited corrosion focused on the UHSS. This galvanic effect was due to a-0.2 V vs. SHE difference in OCP for the UHSS. SVET derived metal loss increased by a factor of >2 for this couple. The localised corrosion observed may reduce the fatigue res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…As the most corroded zone, FZ determined the corrosion resistance of the welded joint [ 27 , 28 ]. In order to further explore the influence of laser welding speed on corrosion, a micro-area SKP test was performed on the laser welding joint to characterize the corrosion resistance of each zone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the most corroded zone, FZ determined the corrosion resistance of the welded joint [ 27 , 28 ]. In order to further explore the influence of laser welding speed on corrosion, a micro-area SKP test was performed on the laser welding joint to characterize the corrosion resistance of each zone.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as the weakest part of TWIP steel components, the welded joint determines the lifetime of TWIP steel components in harsh working environments [ 25 , 26 ]. Due to the unevenness of the structure, the welded joint is sensitive to corrosion, especially galvanic corrosion [ 27 , 28 ]. However, the corrosion behavior of TWIP steel laser-welded joints has rarely been investigated, as no relevant reference has been found.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the preferential site of attack in the HSLA-HSLA couple was the WM zone. [10] The HSLA used in the present work is a marine steel for marine engineering. When a welded structure of HSLA steels is exposed to a marine environment, corrosion becomes a major problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a very limited number is dedicated to understand the local corrosion behaviour of steels used in automotive applications [20].…”
mentioning
confidence: 99%